KLASİK HADİS MECLİS YAPISININ TESPİT VE TAHLİLİ - ALTIN, RUKİYE (Fırat Üniveristesi, 2025)
Dini ilimlerin muhafazası ve aktarımına ev sahipliği yapan mekânlar hadis meclisleri olmuştur. Hadisleri doğru anlamak, bağlamında ele almak ve tatbik etmek için hadislerin aktarım ortamı ve yöntemi önemlidir. Düzenli olarak icra edilen hadis meclisleri dönemin özellikleri dikkate alındığında zihinlerde oldukça ilgi uyandırmaktadır. Çalışmamız birinci asırdan itibaren klasik hadis meclislerinin yapısı ile eğitim-öğretim ortamının nasıllığı üzerine odaklanacaktır. Meclisi oluşturan fiziki yapı, mecliste bulunan hoca ve talebe profili, mecliste gerçekleşen eğitim öğretim faaliyetinde takip edilen yöntemler tespit edilecektir. Böylelikle hadis meclis ortamı tüm yönleriyle ortaya konulmuş olacaktır. Hadis meclis ortamı deyince akla ilk olarak hoca ve talebe gelmektedir. Araştırmamızda, hadis meclisinin bu iki faili başta olmak üzere, kullanılan eğitim materyali, oturma düzeni, dersin başlama ve bitme usulü, mecliste bulunanların sayısı ve yaş dağılımı, hanım râvilerin meclisteki durumu, talebenin soru sorma şekli, hadis meclisinde konuşulan meseleler, hadislerin imlâsı, müstemlî-mümlî ve sâhib diye nitelenen görevlilerin meclisteki durumu, hadis hocasının dersi işleme usulü gibi pek çok konu ele alınacaktır. Böylelikle İslam'ın teşekkül sürecinde hadislerin muhafazasına, yayılmasına ve anlaşmasına katkı sağlayan klasik hadis meclislerinin ortamında gerçekleşen eğitim-öğretim usulü, meclislerde ilim veren hocanın ve ilmin muhatabı olan talebenin uyması gereken kaideler ile inşa ettikleri profil analiz edilecektir. Bununla beraber meclislerde hanımların durumlarına dair de hadis meclis bütünlüğü açısından bazı önemli noktalara dikkat çekilecektir. Bu doğrultuda geçmişten günümüze bir köprü kurularak klasik hadis meclisi örnekliğinde modern meclislere bir nebze olsun ışık tutulmaya çalışılacaktır.

It was the hadith assemblies that served as the venues for the preservation and transmission of religious sciences. In order to understand hadiths correctly, interpret them in their context, and apply them properly, the setting and method of their transmission are of great importance. Hadith assemblies, which were held regularly, arouse considerable interest when the characteristics of the period are taken into consideration. Our study will focus on the structure of classical hadith assemblies from the first century onwards and the nature of the educational environment within them. The physical structure of the assembly, the profiles of the teacher and students present, and the educational methods followed during the sessions will be identified. In this way, the environment of hadith assemblies will be revealed in all its aspects. When we speak of a hadith assembly, the first images that come to mind are the teacher and the student. In this study, we will examine not only these two primary participants of the hadith circle but also a wide range of related elements, such as the educational materials used, the seating arrangement, the protocols for beginning and ending the lesson, the number and age distribution of those present, the presence and roles of female narrators, the manner in which students pose questions, the types of discussions held in the session, the dictation (imlâ) of hadiths, and the roles of key figures such as the mustamli, mumli, and sahib. Moreover, we will analyze the instructional methods of the hadith teacher and the regulations that governed both the teacher and student, shaping their conduct and scholarly persona within the framework of these assemblies. Particular attention will also be given to the participation and status of women in these gatherings, as this constitutes an integral aspect of the holistic structure of hadith assemblies. By examining these elements, we aim to shed light on the educational methods of classical hadith circles, which contributed to the preservation, dissemination, and comprehension of hadith during the formative period of Islam. Ultimately, this study seeks to build a bridge from the past to the present, offering insights that may inspire and inform the design of contemporary scholarly gatherings in the light of classical hadith assemblies.
Identification and analysis of the structure of classical hadith assemblies
Keywords: Din